A perilous proposal : novel - Phillips, Michael R., 1946- (Minneapolis, Minn. : Bethany House Publishers, 2005)
"In a new series related to his bestselling Shenandoah sisters, Michael Phillips returns to the post-Civil War South in a story of forgiveness, danger and love"--Provided by publisher
Includes bibliographical references
Keywords: Reconstruction (U.S. history, 1865-1877) -- Fiction; Women plantation owners -- Fiction; Female friendship -- Fiction; Plantation life -- Fiction; Race relations -- Fiction; Young women -- Fiction; Racism -- Fiction; North Carolina -- Fiction; Fiction